Underwater current distribution induced by spark discharge on a water surface - Midi, Nur Shahida; Ohyama, Ryu-ichiro; Yamaguchi, Shigeru (Elsevier, 2013)
Discharge current distributions generated underwater by spark discharges from the atmosphere to free water surfaces with conductivities in the range 0.07–10.0 S/m were investigated using a laboratory-scale electrode system consists of a discharge electrode and nine underwater grounding electrodes. Discharge emission on the water surface which shows significant change with slight increase in conductivity affects the current distribution in the water. The electric potential of the water surface also changes significantly with slight increase in conductivity. Results of numerical calculations of the underwater discharge current based on the water surface potential agree with the experimental results.